VIRTUAL LEADERSHIP OF ELEMENTARY AND MIDDLE SCHOOL PRINCIPALS DURING PANDEMIC ERA IN MAKASSAR CITY - Wilfredo Dolor Mendoza Jr.,; Muhammad Ardiansyah,; Sulaiman Samad, (International Journal of Social Science, 2023)
In this situation of pandemic, schools have to adjust to the new trends of education wherein most things have to be done online. Different platforms are used to be able to mobilize teachers, parents, students and other stakeholders of the schools in Makassar City. Applications like Zoom, Google-meet, and WhatsApp are just some of the media that so far effective in communicating with those stakeholders. In this research, the researcher aims to determine ways and means on how these principals are able to mobilize and influence all the stakeholders so that goals and objectives of the school will be achieved. Based on the findings, principals have to use various platforms and need to conduct regular meetings to tall these stakeholders to ensure that education is well delivered. This paper applies the descriptive qualitative method wherein data is mainly collected by interviews and observations based on the objective of the research. These data are then reduced and analyzed to come up with a conclusion that is based on the main objective of the researcher